TET-mediated 5hmC in breast cancer: mechanism and clinical potential - Jiahang Zhang; Nadire Aishan; Zhongqiu Zheng; Siwei Ju; Qina He; Qingna Meng; Xixi Lin; Jiaheng Lang; Jichun Zhou; Yongxia Chen; Bojian Xie; Yangjun Cai; et al. (Epigenetics)
Breast cancer is the most common cancer among women, with differences in clinical features due to its distinct molecular subtypes. Current studies have demonstrated that epigenetic modifications play a crucial role in regulating the progression of breast cancer. Among these mechanisms, DNA demethylation and its reverse process have been studied extensively for their roles in activating or silencing cancer related gene expression. Specifically, Ten-Eleven Translocation (TET) enzymes are involved in the conversion process from 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), which results in a significant difference in the global level of 5hmC in breast cancer compared with normal tissues. In this review, we summarize the functions of TET proteins and the regulated 5hmC levels in the pathogenesis of breast cancer. Discussions on the clinical values of 5hmC in early diagnosis and the prediction of prognosis are also mentioned.